Effect of far-infrared radiation on inhibition of colonies on packaging during storage of sterilised surgical instruments - Li-Yun Fann; Chih-Chien Cheng; Yung-Chen Chien; Cheng-Wei Hsu; Wu-Chien Chien; Yao-Ching Huang; Ren-Jei Chung; Shi-Hao Huang; Ying-Hua Jiang; Shih-Han Yin; Kai-Wen Cheng; Yi-Ping Wu; et al. (Scientific Reports, 2023)
Abstract The sterilisation of surgical instruments is a major factor in infection control in the operating room (OR). All items used in the OR must be sterile for patient safety. Therefore, the present study evaluated the effect of far-infrared radiation (FIR) on the inhibition of colonies on packaging surface during the long-term storage of sterilised surgical instruments. From September 2021 to July 2022, 68.2% of 85 packages without FIR treatment showed microbial growth after incubation at 35 °C for 30 days and at room temperature for 5 days. A total of 34 bacterial species were identified, with the number of colonies increasing over time. In total, 130 colony-forming units were observed. The main microorganisms detected were Staphylococcus spp. (35%) and Bacillus spp. (21%) , Kocuria marina and Lactobacillus spp. (14%), and mould (5%). No colonies were found in 72 packages treated with FIR in the OR. Even after sterilisation, microbial growth can occur due to movement of the packages by staff, sweeping of floors, lack of high-efficiency particulate air filtration, high humidity, and inadequate hand hygiene. Thus, safe and simple far-infrared devices that allow continuous disinfection for storage spaces, as well as temperature and humidity control, help to reduce microorganisms in the OR.